2005
DOI: 10.1038/nature03847
|View full text |Cite
|
Sign up to set email alerts
|

Licensing of natural killer cells by host major histocompatibility complex class I molecules

Abstract: Self versus non-self discrimination is a central theme in biology from plants to vertebrates, and is particularly relevant for lymphocytes that express receptors capable of recognizing self-tissues and foreign invaders. Comprising the third largest lymphocyte population, natural killer (NK) cells recognize and kill cellular targets and produce pro-inflammatory cytokines. These potentially self-destructive effector functions can be controlled by inhibitory receptors for the polymorphic major histocompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,300
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,156 publications
(1,386 citation statements)
references
References 30 publications
63
1,300
2
9
Order By: Relevance
“…These features, together with high expression of cytolytic molecules, allow CD56 dim NK cells to efficiently lyse target cells either directly or indirectly through CD16‐mediated antibody‐dependent cellular cytotoxicity (ADCC). The expression of a family of receptors called killer immunoglobulin‐like receptors (KIRs), which modulate the responsiveness of NK cells to activating receptor ligation,62, 63 is also restricted to CD56 dim NK cells.…”
Section: Subsets Of Nk Cellsmentioning
confidence: 99%
“…These features, together with high expression of cytolytic molecules, allow CD56 dim NK cells to efficiently lyse target cells either directly or indirectly through CD16‐mediated antibody‐dependent cellular cytotoxicity (ADCC). The expression of a family of receptors called killer immunoglobulin‐like receptors (KIRs), which modulate the responsiveness of NK cells to activating receptor ligation,62, 63 is also restricted to CD56 dim NK cells.…”
Section: Subsets Of Nk Cellsmentioning
confidence: 99%
“…However, such NK cells are self-tolerant because they are hyporesponsive after engagement of activating receptors. Conversely, NK cells that express inhibitory receptors for self-MHC are functionally competent [3,4]. Thus, in humans, it has been shown that KIR2DL2/L3 1 , KIR2DL1 1 or KIR3DL1 1 CD56 dim NK cells derived from donors expressing the corresponding HLA class I ligands (group C1 alleles, group C2 alleles and HLA allotypes with the Bw4 epitope, respectively) are more responsive to CD16 cross-linking and stimulation with class I negative target cells than other NK-cell subsets [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…At the immature DX5 -stage, NK cells express multiple NK receptors including CD94/NKG2, NKG2D and NKp46, but are unable to perform granule-mediated cytotoxicity [21][22][23]. During maturation to DX5 + mature cells, NK cells start to express Ly49 MHC class I receptors [22][23][24], and undergo an education process during which NK cells expressing inhibitory receptors that recognize self MHC class I are "licensed" to perform more potent effector functions [25][26][27][28].cd T cells, like ab T cells, develop in the thymus, where V(D)J recombination of TCR genes occurs. Using T cell receptor d locus-histone 2B-enhanced GFP (Tcrd-H2BEGFP) knock-in mice in which an IRES-controlled H2B-EGFP fusion protein is present in the 3 0 untranslated region of the Tcrd constant gene [29], we have recently shown that developing cd T cells undergo a "TCR quality control checkpoint" upon successful expression of TCRcd.…”
mentioning
confidence: 99%